Cross-Reactivity of TCR Repertoire: Current Concepts, Challenges, and Implication for Allotransplantation - Degauque, Nicolas; Brouard, Sophie; Soulillou, Jean-Paul (Frontiers in Immunology, 2016)
Being able to track donor reactive T cells during the course of organ transplantation is key to improve the graft survival, to prevent graft dysfunction and to adapt the immunosuppressive regimen. The attempts of transplant immunologists have been for long hampered by the large size of the alloreactive T cell repertoire. Understanding how self-TCR can interact with allogeneic MHC is key to critically appraise the different assays available to analyze the TCR Vβ repertoire usage. In this report, we will review conceptually and experimentally the process of cross-reactivity. We will then highlight what can be learned from allotransplantation, a situation of artificial cross-reactivity. Finally, the low- and high-resolution techniques to characterize the TCR Vβ repertoire usage in transplantation will be critically discussed.